2012
DOI: 10.1136/bcr-2012-007559
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of consciousness and involuntary movements caused by pregabalin

Abstract: SUMMARYA 91-year-old man with chronic low-back pain presented with 1-day history of disturbance of consciousness and myoclonus of all of his extremities and face. Laboratory examinations revealed no abnormalities. Administration of benzodiazepine for the myoclonus resulted in immediate and complete disappearance of the symptoms. He recently started taking pregabalin (Lyrica capsules) which was prescribed for low-back pain 3 days ago. The day following admission, he discontinued pregabalin. He did not experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For the years 1999 and 2019, a total of 46 reports containing 305 cases who developed MDs after the use of PGB from 17 different countries were reported [ Table 1 ]. [ 2 3 10 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 ] The origin was North American in 196, European in 68, Asian in 40, and South American in 1. The MDs associated with PGB found were as follows: 184 patients with ataxia, 61 with tremors, 39 with MCL, 8 with parkinsonism, 1 with restless legs syndrome, 1 with dystonia, 1 with dyskinesia, and 1 with akathisia.…”
Section: Resultsmentioning
confidence: 99%
“…For the years 1999 and 2019, a total of 46 reports containing 305 cases who developed MDs after the use of PGB from 17 different countries were reported [ Table 1 ]. [ 2 3 10 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 ] The origin was North American in 196, European in 68, Asian in 40, and South American in 1. The MDs associated with PGB found were as follows: 184 patients with ataxia, 61 with tremors, 39 with MCL, 8 with parkinsonism, 1 with restless legs syndrome, 1 with dystonia, 1 with dyskinesia, and 1 with akathisia.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases it was shown that add-on therapy of pregabalin can induce myoclonus in patients with seizure history. In patients with renal failure pregabalin also can evoke myoclonic seizures [11][12][13].…”
Section: Discussionmentioning
confidence: 99%